The effect of zinc deficiency and iron overload on endocrine and exocrine pancreatic function in children with transfusion-dependent thalassemia: a cross-sectional study - Suzan O. Mousa; Ebtihal M. Abd Alsamia; Hend M. Moness; Osama G. Mohamed (BMC, 2021)
Abstract Background Children with transfusion-dependent thalassemia (TDT) suffer from secondary hemosiderosis and the delirious effects this iron overload has on their different body organs, including the pancreas. They are also more prone to develop zinc deficiency than the general pediatric population. This study aimed to determine the effect of zinc deficiency and iron overload on the endocrine and exocrine pancreas in TDT children. Methods Eighty children, already diagnosed with TDT, were included in this study. We assessed the following in the participant children: serum ferritin, serum zinc, endocrine pancreatic function (oral glucose tolerance test (OGTT), fasting insulin level and from them, HOMA-IR was calculated), and exocrine pancreatic function (serum lipase and serum amylase). Results Forty-four TDT children had a subnormal zinc level, while 36 of them had a normal serum zinc level. TDT children with low serum zinc had significantly more impaired endocrine pancreatic function and an abnormally high serum lipase than children with normal serum zinc, p < 0.05 in all. Serum zinc was significantly lower in TDT children with serum ferritin above the ferritin threshold (≥2500 ng/ml) than those below (59.1 ± 20.2 vs. 77.5 ± 28.13), p = 0.02. TDT children, having a serum ferritin ≥2500 ng/ml, had significantly more frequently impaired endocrine pancreatic function and abnormally high serum lipase than TDT children below the ferritin threshold, p < 0.05 in all. Conclusion In children with transfusion-dependent thalassemia, zinc deficiency aggravates iron-induced pancreatic exocrine and endocrine dysfunction.